FEASIBILITY STUDY (FS) RENCANA KOLAM RETENSI SUBDAS LAMBIDARO DI JALAN MAJU BERSAMA I KELURAHAN TALANG KELAPA KECAMATAN ALANG-ALANG LEBAR - Yusuf, M. Syoeib (Kohesi: Jurnal Sains dan Teknologi, 2025)
Retention ponds are usually built in flood-prone areas or along rivers or drainages, and are designed to accommodate large amounts of rainwater without causing damage to the surrounding environment. Retention ponds are one of the water resource management infrastructures that function to temporarily accommodate and store rainwater or surface runoff to prevent flooding and improve water quality before being discharged into drainage systems or other water bodies. Retention ponds are usually designed with a certain depth and capacity to be able to control excessive water flow, especially in urban areas with high levels of hardening. In addition, retention ponds also play a role in water conservation, maintaining aquatic ecosystems, and improving environmental aesthetics through greening and biodiversity. In urban drainage systems, the most effective and efficient way to deal with flooding in an area is by creating a retention pond. A retention pond is a structure or facility used to accommodate and regulate the flow of rainwater or surface runoff, especially during high rainfall. This pond functions to reduce the volume and speed of water flow to drainage channels or other water bodies, with the aim of avoiding flooding and maintaining the stability of the drainage system. The inundation that occurred in the Lambidaro SUB DAS area on the street Maju Bersama 1, Talang Kelapa Village, Alang-alang Lebar District was caused by high rainfall and also because the topography of the area was relatively flat and there were many depressions due to changes in land use. It is expected that the plan to create a retention pond in the Lambidaro Sub-DAS on the street Maju Bersama I, Talang Kelapa Village, Alang-alang Lebar District can provide economical and environmentally friendly study results for the plan to create a Retention Pond in the Lambidaro Sub-DAS on the street Maju Bersama I, Talang Kelapa Village, Alang-alang Lebar District and also obtain images of the potential, utilization and development of the river area so that it can be made so that it is expected to prevent flooding and other interests.